Dihydrotanshinone I Alleviates Crystalline Silica-Induced Pulmonary Inflammation by Regulation of the Th Immune Response and Inhibition of STAT1/STAT3 - Yiting Zhang; Chao Li; Siyi Li; Yiping Lu; Sitong Du; Xinning Zeng; Xi Chen; Jie Chen (Mediators of Inflammation)
Occupational exposure to crystalline silica (CS) results in a persistent pulmonary inflammatory response that eventually leads to abnormal tissue repair, disability, and death. The inflammatory-immune responses occur in the early stages of CS exposure, and both innate and adaptive immunity are involved. CD4+ T cells play a pivotal role in the pathogenesis of CS-induced pulmonary disease, which has no proven curative therapy. Dihydrotanshinone I (DHI), a natural product isolated from Salvia miltiorrhiza Bunge (Danshen), has anti-inflammatory and immunomodulatory properties. However, whether DHI has a protective effect on CS-induced lung disease, how it influences the Th immune response, and the potential underlying molecular mechanism(s) have not been fully clarified. In this study, DHI treatment of CS-exposed mice reduced the expression of proinflammatory cytokines and the infiltration of immune cells. It significantly ameliorated CS-induced pulmonary inflammation by attenuating T helper (Th)1 and Th17 responses, which were tightly related to the inhibition of STAT1 and STAT3. DHI significantly altered Th2 cytokines but not the Th2 nuclear transcription factor. Furthermore, our study found that DHI treatment also affected regulatory T cell activity in CS-injured mice. Taken together, our findings indicated that DHI could modulate Th responses and alleviate CS-induced pulmonary inflammation, suggesting a novel application of DHI in CS-induced pulmonary disease.